Effects of Dietary Supplementation with Copper Sulfate or Tribasic Copper Chloride on Carcass Characteristics, Tissular Nutrients Deposition and Oxidation in Broilers - Xiang-Qi, Zhang; Zhang, Ke-Ying; Ding, Xue-Mei; Bai, Shi-Ping (Pakistan Journal of Nutrition, 2009)
The experiment was conducted to compare the effects of dietary Tribasic Copper Chloride (TBCC) and Copper Sulfate (CuSO4) on carcass characteristics, copper deposition and tissular nutrients oxidation in broilers. A 2x5 factorial (two copper sources: CuSO4 or TBCC; five added copper levels as 0, 50, 150, 250 or 350 mg/kg) completely randomized design was conducted in experiment. 1,890, 1 day old, Cobb 48 commercial male chicks were randomly allotted into 63 floor pens of 30 birds each and fed to 40-days-old. Two birds from each pen were sacrificed. Their carcass characteristics and the contents of crude fat, copper, VE or Malondialdehyde (MDA) in tissues were determined. Results indicated that: when added copper level was 150 mg/kg, half-evisceration yield and breast yield of broilers increased. The evisceration yield of broilers was raised by feeding TBCC and supplementation with 50 mg/kg copper from TBCC got the biggest evisceration yield; when added copper levels increased from 50-350 mg/kg, contents of copper or crude fat in liver or muscles and the level of VE in heart were increased significantly, while, the levels of VE or MDA in liver decreased; when added copper levels were less than or equal to 150 mg/kg, the copper levels in liver or muscles were similar between copper sources; while added copper levels were >150 mg/kg, the smaller quantities of copper in liver were gained by using TBCC comparing with feeding CuSO4. It implicated that TBCC was a safe dietary copper source.